2015
DOI: 10.1038/srep13054
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a drug targeting microenvironmental support for lymphoma cells by screening using patient-derived xenograft cells

Abstract: Cell lines have been used for drug discovery as useful models of cancers; however, they do not recapitulate cancers faithfully, especially in the points of rapid growth rate and microenvironment independency. Consequently, the majority of conventional anti-cancer drugs are less sensitive to slow growing cells and do not target microenvironmental support, although most primary cancer cells grow slower than cell lines and depend on microenvironmental support. Here, we developed a novel high throughput drug scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…We have previously reported that the BLS4 mouse FRC line, which was established from a mouse lymph node, 26 enabled culture of PDX lymphoma cells 21 and that CAF also supported survival of primary patient lymphoma cells in vitro. 22 Primary patient lymphoma cells (Pt#8 with Burkitt lymphoma, and Pt#9 with high-grade B-cell lymphoma, not otherwise specified) could proliferate in coculture with CAF#1 and CAF#2 in vitro, whereas neither cell type could survive in monoculture (Figure 2A,B; Table S2).…”
Section: Support Of Tumor Cell Survival By Cafmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that the BLS4 mouse FRC line, which was established from a mouse lymph node, 26 enabled culture of PDX lymphoma cells 21 and that CAF also supported survival of primary patient lymphoma cells in vitro. 22 Primary patient lymphoma cells (Pt#8 with Burkitt lymphoma, and Pt#9 with high-grade B-cell lymphoma, not otherwise specified) could proliferate in coculture with CAF#1 and CAF#2 in vitro, whereas neither cell type could survive in monoculture (Figure 2A,B; Table S2).…”
Section: Support Of Tumor Cell Survival By Cafmentioning
confidence: 99%
“…[15][16][17][18][19][20] In malignant lymphoma, we have previously reported that a mouse-derived fibroblastic reticular cell (FRC) line supported lymphoma cells from patient-derived xenograft (PDX) models, indicating that fibroblasts also play many functional roles in the lymphoma microenvironment. 21,22 This report examined how CAF isolated from primary lymphoma samples support primary lymphoma cells in vitro and clarified the components vital for these abilities.…”
Section: Introductionmentioning
confidence: 99%
“…Toward this end, Sugimoto and colleagues have demonstrated that the co-culture of BLS4 fibroblast reticular mouse cell lines strongly sustained PDTX primary cell viability, allowing an effective ex vivo screening with a library of 2613 compounds. Interestingly, using this approach the authors found a metabolic dependency and identify a novel Achilles' heel of lymphoma cells which could be effectively targeted by the pyruvinium pamoate (PP), an FDA-approved classical anthelminthic compound, inhibiting glutathione-mediated pathways [26]. In the recent years a plethora of studies have been clearly shown the effectiveness of these models in many different arenas.…”
Section: Pdtx Models For Drug Discoverymentioning
confidence: 99%
“…Therefore PDTX can be used not only to study tumor cells, but also to investigate the role and function of the stroma/host, providing new opportunities to explore and dissect the protumorigenic role of cancer niches. Collectively, several studies have now demonstrated that PDTX represent effective models to test drugs that target cancer elements and modulate tumor vasculature and/or the stromal compartment [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…These inevitably lead to graft‐versus‐host disease and eventually to the mouse demise. With the case of diffuse large B‐cell lymphoma, still few well characterised models exist, which somehow appear to mimic donor tumor genetics and response, thus some high throughput drug discovery trials through our group and Sugimoto et al have shown their promising potential . Perhaps the most difficult PDTX to generate is the space of peripheral T‐cell lymphoma .…”
mentioning
confidence: 99%